Evaluation of three molecular methods for tracking and identifying HER2/neu oncogene in breast cancer patients - González Niño, Leonel Andrés; Helena Aristizábal Bernal, Beatriz Helena (Medicina UPB, 2010)
Objective: to compare IHC, FISH and quantitative real-time PCR techniques, in the determination of HER2/neu oncogene amplification and overexpression in 70 breast cancer patients.Methods: we evaluated the performance of the IHC HercepTest and quantitative real-time PCR techniques, using as a gold standard the fluorescent in situ hybridization technique. We determined the positivity percentage of the breast neoplasms that have the amplification for HER2/neu oncogene.Results: 38% of breast tumors demonstrate amplification of HER2/neu oncogene according to real-time PCR and we found an 80% concordance for real-time PCR and FISH in cases classified as equivocal or grade 2+ with IHC.Conclusion: the results of this study suggest that the analysis by real-time PCR is a valid alternative in cases when it is not possible to use the FISH technique for reassessment of breast neoplasms classified as equivocal or grade 2+ for HER2/neu with IHC. The combination of IHC and quantitative real-time PCR may be a good approach in the determination of the expression and amplification status of HER2/neu in breast cancer patients.
Keywords: breast neoplasms; in situ hybridization, fluorescence; immunohistochemistry; HER2/neu; real-time PCR